Answer to Question #208896 in Differential Equations for deku

Question #208896

EXACT DIFFERENTIAL EQUATIONS


Test for exactness and find the general solution:

1. (2x + 4y − 5)dx + (6y + 4x − 1)dy = 0

2. (y + 2xy3)dx + (1+ 3x2y2 + x)dy = 0

3. 3x2ydx + (x3 + 2y4)dy = 0

4. (1/y)dx - (x/y2)dy = 0

5. (4x3 − y3)dx − 3xy2dy = 0


1
Expert's answer
2021-06-21T14:13:45-0400

1.


"(2x + 4y \u2212 5)dx + (6y + 4x \u2212 1)dy = 0"

"\\dfrac{\\partial Q}{\\partial x}=4, \\dfrac{\\partial P}{\\partial y}=4"

The given equation is exact because the partial derivatives are the same:


"\\dfrac{\\partial Q}{\\partial x}=4=\\dfrac{\\partial P}{\\partial y}"

We have the following system of differential equations to find the function "u(x, y)"


"\\begin{cases}\n \\dfrac{\\partial u}{\\partial x}=2x + 4y \u2212 5 \\\\\n\\\\\n \\dfrac{\\partial u}{\\partial y}=6y + 4x \u2212 1 \n\\end{cases}"

"u(x, y)=\\int (2x + 4y \u2212 5)dx=x^2+4xy-5x+\\varphi (y)"

"\\dfrac{\\partial u}{\\partial y}=4x+\\varphi' (y)=6y + 4x \u2212 1"

"\\varphi' (y)=6y \u2212 1"

The general solution of the exact differential equation is given by


"x^2+4xy-5x+3y^2-y=C"

where "C" is an arbitrary constant.


2.


"(y + 2xy^3)dx + (1+ 3x^2y^2 + x)dy = 0"

"\\dfrac{\\partial Q}{\\partial x}=6xy^2+1, \\dfrac{\\partial P}{\\partial y}=1+6xy^2"

The given equation is exact because the partial derivatives are the same:


"\\dfrac{\\partial Q}{\\partial x}=6xy^2+1=\\dfrac{\\partial P}{\\partial y}"

We have the following system of differential equations to find the function "u(x, y)"

"\\begin{cases}\n \\dfrac{\\partial u}{\\partial x}=y + 2xy^3 \\\\\n\\\\\n \\dfrac{\\partial u}{\\partial y}=1+ 3x^2y^2 + x\n\\end{cases}"

"u(x, y)=\\int (y + 2xy^3)dx=xy+x^2y^3+\\varphi (y)"

"\\dfrac{\\partial u}{\\partial y}=x+3x^2y^2+\\varphi' (y)=1+ 3x^2y^2 + x"

"\\varphi' (y)= 1"



The general solution of the exact differential equation is given by


"xy+x^2y^3+y=C"

where "C" is an arbitrary constant.


3.


"3x^2ydx + (x^3+2y^4)dy = 0"

"\\dfrac{\\partial Q}{\\partial x}=3x^2, \\dfrac{\\partial P}{\\partial y}=3x^2"

The given equation is exact because the partial derivatives are the same:


"\\dfrac{\\partial Q}{\\partial x}=3x^2=\\dfrac{\\partial P}{\\partial y}"

We have the following system of differential equations to find the function "u(x, y)"

"\\begin{cases}\n \\dfrac{\\partial u}{\\partial x}=3x^2y \\\\\n\\\\\n \\dfrac{\\partial u}{\\partial y}=x^3+2y^4 \n\\end{cases}"

"u(x, y)=\\int 3x^2ydx=x^3y+\\varphi (y)"

"\\dfrac{\\partial u}{\\partial y}=x^3+\\varphi' (y)=x^3+2y^4"

"\\varphi' (y)=2y^4"



The general solution of the exact differential equation is given by


"x^3y+\\dfrac{2}{5}y^5=C"

where "C" is an arbitrary constant.


4.


"(\\dfrac{1}{y})dx - (\\dfrac{x}{y^2})dy = 0"

"\\dfrac{\\partial Q}{\\partial x}=-\\dfrac{1}{y^2}, \\dfrac{\\partial P}{\\partial y}=-\\dfrac{1}{y^2}"

The given equation is exact because the partial derivatives are the same:


"\\dfrac{\\partial Q}{\\partial x}=-\\dfrac{1}{y^2}=\\dfrac{\\partial P}{\\partial y}"

We have the following system of differential equations to find the function "u(x, y)"


"\\begin{cases}\n \\dfrac{\\partial u}{\\partial x}=\\dfrac{1}{y} \\\\\n\\\\\n \\dfrac{\\partial u}{\\partial y}=-\\dfrac{x}{y^2}\n\\end{cases}"

"u(x, y)=\\int (\\dfrac{1}{y})dx=\\dfrac{x}{y}+\\varphi (y)"

"\\dfrac{\\partial u}{\\partial y}=-\\dfrac{x}{y^2}+\\varphi' (y)=-\\dfrac{x}{y^2}"

"\\varphi' (y)=0"

The general solution of the exact differential equation is given by


"\\dfrac{x}{y}=C"

where "C" is an arbitrary constant.


5.


"(4x^3-y^3)dx - (3xy^2)dy = 0"

"\\dfrac{\\partial Q}{\\partial x}=-3y^2, \\dfrac{\\partial P}{\\partial y}=-3y^2"

The given equation is exact because the partial derivatives are the same:


"\\dfrac{\\partial Q}{\\partial x}=-3y^2=\\dfrac{\\partial P}{\\partial y}"

We have the following system of differential equations to find the function "u(x, y)"

"\\begin{cases}\n \\dfrac{\\partial u}{\\partial x}=4x^3-y^3 \\\\\n\\\\\n \\dfrac{\\partial u}{\\partial y}=-3xy^2 \n\\end{cases}"

"u(x, y)=\\int (4x^3-y^3)dx=x^4-xy^3+\\varphi (y)"

"\\dfrac{\\partial u}{\\partial y}=-3xy^2+\\varphi' (y)=-3xy^2"

"\\varphi' (y)=0"


The general solution of the exact differential equation is given by


"x^4-xy^3=C"

where "C" is an arbitrary constant.



Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog